Influence of early biliary complications on survival rates after pediatric liver transplantation—A positive outlook. (29th June 2021) - Berchtold, Valeria; Messner, Franka; Weissenbacher, Annemarie; Oberhuber, Rupert; Entenmann, Andreas; Aldrian, Denise; Vogel, Georg; Margreiter, Christian; Ulmer, Hanno; Krapf, Johanna; Cardini, Benno; Schlitt, Hans J.; et al.
Abstract: Background: Early biliary complications (EBC) constitute a burden after pediatric liver transplantation frequently requiring immediate therapy. We aimed to assess the impact of EBC on short‐ and long‐term patient and graft survival as well as post‐transplant morbidity. Methods: We analyzed 121 pediatric liver transplantations performed between 1984 and 2019 at the Medical University of Innsbruck for the occurrence of early (<90 days) biliary complications and investigated the influence of EBC on patient and graft survival. Results: Early biliary complications occurred in 30 (24.8%) out of the 121 pediatric liver transplant recipients. Patient survival at 15 years (89.2% vs. 84.2%, p = .65) and all‐cause (82.5% vs. 74.0%) and death‐censored graft survival (82.5% vs. 75.1%, p = .71) at 10 years were similar between the EBC and the non‐EBC group. The EBC group had a significantly longer ICU (25 vs. 16 days, p < .001) and initial hospital stay (64 vs. 42 days, p = .002). Livers of patients with EBC were characterized by multiple bile ducts (33.3% vs. 13.2%, p = .027), and patients with EBC had a higher risk to develop late biliary complications (OR 2.821 [95% CI 1.049–7.587], p = .044) and bowel obstruction/perforation (OR 4.388 [95% CI 1.503–12.812], p = .007). Conclusion: Early biliary complications after pediatric liver transplantation is frequent. The occurrence of EBC significantly increased post‐transplant morbidity without affecting mortality. Multiple bile ducts were the only risk factor for the development of EBC in our cohort.